Struktur Kandelia candel (L.) Druce di Pulau Payung Sungsang, Banyuasin, Sumatera Selatan - Sarno, Sarno; Marisa, Hanifa; Army, Fadilla Surya (MAKILA, 2020)
K. candel (L.) Druce, including one of the rare mangroves that need unique management. This study aimed to determine the vegetation structure, habitat, and abundance of K. candel. Determination of stations and points of research transects using the line transect method at five observation stations with each observation station consisting of three transect lines. The results showed that 13 species from 8 families were divided into primary, minor, and association mangrove categories. K. candel habitat in Pulau Payung was found at observation station 2 with a salinity of 0 ‰ and a clay substrate type. K. candel was also found at observation station 4 with a 0% salinity and a sandy clay substrate type. The vegetation that dominates on Payung Island is the A.alba BI type. seen from the Importance Value (NP) at the tree level of 77.77%, sapling level of 86.67%, and at the seedling level of 65.52%. The significance value of K. cande at the tree level was 30.59%, the sapling level was 47.33%, and at the seedling, the level was 24.48%. This suggests that the abundance of K. Candel is limited.